Empowerment of Micro/ Small/ Medium Enterprises in Making Traditional Herbal from Family Medicinal Plants as an Effort to Achieve SDGs - Nhestricia, Nhadira; Utami, Novi Fajar; Sulistiyono, Fitria Dewi; Riswana, Dea Putri; Putra, Agita Detia (Jurnal Pengabdian Masyarakat Inovatif, 2024)
Cikarawang Village, Dramaga District, Bogor Regency has a Merdesa community which engaged in plantations. This community has become micro/small/medium enterprises (MSMEs) but has not been able to significantly improve the welfare of the community in achieving Sustainable Development Goals (SDGs). The purpose of this activity is to be able to develop the home yards of the Cikarawang Village community to be more useful, the second can increase the community's production sector, and the last is expected to increase the birth of MSMEs in Cikarawang Village. This program is also carried out in collaboration with the Kebun Merdesa Community. Herbs are the community's choice in curing diseases, and some even cultivate herbs as Family Medicinal Plants or commonly referred to as Family Medicinal Plants. The Family Medicinal Plants area around the community's yard area can easily obtain medicinal plants which are then processed into herbal medicine. This program will also involve education units. Promotional media in the form of banners, billboards, and banners will be made and installed in strategic locations towards partners to complement this program which is also a means of information for the village community. This activity involved 2 lecturers and 2 students from Pharmacy Bachelor Program with combined the program of Freedom of Learning Independent Campus which oriented towards community service. The formation of micro-business units in Cikarawang Kebun Merdesa Village, increasing the productivity and creativity of Cikarawang Village’s youth, and also providing added value economically, socially, and culturally were implemented.